PENGARUH BRAND IMAGE, HARGA , DAN VIRAL MARKETING TERHADAP MINAT BELI HIJAB DI VARISHA OFFICIAL SHOP: STUDI KASUS GEN Z KOTA PALEMBANG - Brenda Aurora; Bunga Mar’atush Shalihah; Safitri Asrol (Jurnal Ekonomi dan Bisnis Nias Selatan, 2026)
The growth of hijab sales through online media has made consumers, especially Generation Z, increasingly selective in choosing products. Varisha Official Shop is a well-known hijab brand in Palembang. This study aims to determine the influence of brand image, price, and viral marketing on hijab purchase intention at Varisha Official Shop among Generation Z in Palembang. This study uses a quantitative method with multiple linear regression analysis processed with SPSS version 26. Data were obtained from 96 respondents through purposive sampling techniques. Before the analysis was carried out, the data had been tested through validity, reliability, and classical assumption tests (normality, linearity, multicollinearity, heteroscedasticity), as well as multiple linear analysis to test the hypothesis partially, simultaneously, and the coefficient of determination (R2) test. The regression model obtained was Y = 6.100 + 0.243 – 0.040 + 0.884. The results of the study indicate that partially, brand image and viral marketing have a positive and significant effect on purchase intention, while price has no significant effect. However, simultaneously, all three variables significantly influence purchase intention, as evidenced by the calculated F value > F table (45.730 > 2.70) with a significance level of 0.000. The R2 value of 0.585 indicates that 58% of the variation in purchase intention can be explained by these three variables, while the remainder is influenced by other factors outside this study.